Initial rotational velocity of hips is a key factor in discus throw - Yamamoto, D.; Ito, A. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
The purpose of this study was to investigate relationships between the official discus throwing distance and the movements of discus throw or the release conditions of discus. The throwing movements of 18 male discus throwers were recorded by two digital video cameras (60 Hz) in the 11th World Championships in Athletics in Osaka and the Japan Track and Field National Championships, and also in experimental trials. From the video data of trials when each athlete had thrown the longest distance, real-life three-dimensional coordinates of their body landmarks and the center of the discus were calculated with the direct linear transformation method. The throwing movements were divided into six instants and analyzed. The initial velocity and the height of discus at the moment of release showed a positive correlation with the throwing distance. The throwing distance had no relation with the release height normalized by the body height and the release angle. These results suggested that the initial velocity and the release height of discus must be important to take longer throws, however the release height was dependent on the body height. At the right-foot takeoff (R-off) and the left-foot touchdown (L-on), both discus velocity and rotational velocity of hips indicated positive correlations with the throwing distance. Positive relations were shown between the discus velocity at R-off and rotational velocity of shoulders and hips at the same instants. The discus velocity at L-on had a positive relationship with the rotational velocity of shoulders at that time. The higher discus velocity at R-off of longer-distance throwers suggested that increase of rotational velocity of the whole body at the beginning of throwing movements is important. The translational velocity of the center of mass including thrower and discus (CM) at left-foot takeoff (L-off), right-foot touchdown (R-on) and L-on were recognized as a negative correlation with the official distance. The translational velocity of CM showed a negative relation with the rotational velocity of hips at L-off, and also velocity of CM indicated a negative correlation with torsion angle of trunk at R-on. These results suggested that longer-distance throwers might keep lower translational velocity of CM to obtain lager torsion angle of trunk during the flight phase. These findings were concluded as follows. Differences in movements which determine throwing distance appeared from the beginning of throwing movements. That is, it is necessary for throwers to increase discus velocity with rotational velocities of shoulders and hips from the initial phase of throwing. At the middle phase, to maintain a lower translational velocity of CM must obtain higher rotational velocity of hips, and thus a larger torsion angle of trunk is produced by the higher rotational velocity of hips. The increase of rotational velocity of hips, shoulders and arm swing occurred in order during the final phase before discus release.